Avaliação de grãos de milheto (Pennisetum glaucum) na alimentação de coelhos em crescimento - Catelan, Fernanda (2010)
Four experiments were carried out in order to evaluate the nutritive value and the performance of growing rabbits fed with isoenergetic diets containing different pearl millet levels (Pennisetum glaucum) ADR 7010, ensiled with or without inoculant. The first experiment was carried out in order to evaluate the nutritive value of pearl millet levels fed to growing rabbits. In digestibility evaluation the nutritive values of pearl millet were determined for 22 New Zealand White rabbits, male and female, 45 days old, allotted in a completely randomized design, with two treatments, a reference diet and test diet composed of 70% of its volume by reference diet and 30% of pearl millet and with 11 replications. The apparent digestibility of DM (%), CP (%), NDF (%), ADF (%) and GE (%) of the pearl millet were 88.71, 85.39, 24.35, 18, 56 and 75.02, and their digestible values were 81.25, 11.77, 4.28, 0.63 and 3361 kcal/kg. The second experiment evaluated the performance of growing rabbits fed with isoenergetic diets containing different pearl millet levels. There were used 120 New Zealand White rabbits, 60 males and 60 females, with 32 days of age and allotted in a completely randomized design with six treatments, with 10 replications and two animals each one. The diets were formulated containing increased levels of pearl millet (0, 20, 40, 60, 80 and 100%) in substitution of the corn from reference diet. No differences were observed in the daily feed intake, the daily weight gain, the feed conversion, the carcass traits and the feed cost per kilogram of produced rabbit, when corn was replaced by pearl millet in feeds for rabbits, based on the digestible energy. It may be concluded that pearl millet has good nutritive value and may replace corn in growing rabbits diets. The third experiment was carried out in order to evaluate the nutritive value of growing rabbits fed with isoenergetic diets containing different pearl millet levels ensiled with or without inoculant enzimo-bacteriano Bacto Silo Máster Tropical through a digestibility assay the nutritive values of pearl millet were determined for 30 New Zealand White rabbits, 15 males and 15 females, 45 days old, allotted in a completely randomized design, with three treatments and ten replications. The use of inoculant did not increase the coefficients digestibility of pearl millet. The coefficients of apparent digestibility of DM (%), CP (%) NDF (%), ADF (%) and GE (%) of millet ensiled with and without inoculant were 93.07, 90.63, 14.51, 19.83, 78.98 and 91.13, 85.26, 32.56, 17.66, 76.72, respectively and the digestible values were 90.17 and 88.74; 12.79 and 12.41; 3.31 and 7.3; 0.51 and 0.46; 3547 and 3427, respectively. The fourth experiment evaluated the performance of growing rabbits fed with isoenergetic diets containing different pearl millet levels ensiled with or without inoculant enzimo-bacteriano Bacto Silo Máster Tropical. 220 New Zealand White rabbits (males and females) with 32 days of age were used and allocated in a completely randomized design, with 11 treatments (diets containing increased levels of pearl millet cultivar ensiled with or without inoculants) substituting the corn (20, 40, 60, 80 and 100% digestible energy) and ten replications with two animals each one. No differences were observed (P>0.05) in growing rabbits performance when pearl millet ensiled with or without inoculant replaced the corn. It may be concluded that the ensiled pearl millet has good nutritive value and millet silage with and without inoculant may replace corn in growing rabbits diets. When this grain for silage is used in rabbits diets do not need the addition of inoculant